1995
DOI: 10.1159/000244242
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Effects after Surfactant Treatment in Premature Infants with Severe Respiratory Distress Syndrome

Abstract: To understand the mechanisms behind the improved oxygenation after intratracheal surfactant instillation, the immediate effects on lung volume and pulmonary mechanics were analyzed. All infants studied were enrolled in multicenter trials in which surfactant therapy was instituted according to a rescue protocol. Infants received either synthetic surfactant (Exosurf) or modified porcine surfactant (Curosurf). Measurements of lung volume and pulmonary mechanics were successfully performed in 12 patients with a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
1
6
1
Order By: Relevance
“…In contrast to animal studies [1,33,42], those in human neonates have failed to demonstrate early improvement of compliance [4,7,11,14,15,19,20,24]. Also in this study, statistical improvement in CRS was not found immediately after surfactant replacement.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…In contrast to animal studies [1,33,42], those in human neonates have failed to demonstrate early improvement of compliance [4,7,11,14,15,19,20,24]. Also in this study, statistical improvement in CRS was not found immediately after surfactant replacement.…”
Section: Discussioncontrasting
confidence: 93%
“…The results from the present study regarding FRC and CRS in infants with severe RDS are comparable to those reported previously [11,16,19,20,24,39]. Our data confirm that infants with severe RDS have non-compliant [18,43], low volume lungs [24,26,32,43].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…82 Increases in FRC pre-and post surfactant treatment are physiologically and clinically highly relevant. [85][86][87][88][89] Interestingly, the improvement in FRC is not paralleled by improved respiratory system compliance (C rs ), and sC rs may even decrease, prompting conclusions that surfactant primarily results in expiratory stabilization of previously aerated alveoli, followed by a slow improvement in C rs after recruitment of new alveoli. 85,[88][89][90] Results of these studies suggest that assessment of C rs (i.e., postsurfactant administration) should always be related to the actual FRC (sC rs ) to avoid misinterpretation.…”
Section: The Extent To Which Functional Findings Can Be Related To Pamentioning
confidence: 99%